Heat Transfer Augmentation: Experimental Study with Nanobubbles Technology - Prudhvi Krishna Amburi; G. Senthilkumar; Ibsa Neme Mogose (Advances in Materials Science and Engineering)
The experimental research on heat transfer characteristics is an ever-ending scheme since the life of all thermoelectronic devices relies on the effective management of thermal energy. In some cases, the gradient of temperature for heat transfer is to be minimum to avoid energy loss, but also there are numerous applications where the requirement of heat transfer to be maximum and could be achieved with a higher temperature difference between the heat transfer medium. In our current research, distilled water-ethylene glycol heat transfer fluid (HTF) was tested with different inlet mass flow rates and temperature as the hot fluid. Atmospheric air was chosen as the cold fluid. The natural convection heat transfer rate between hot and cold fluid streams was analyzed with and without the generation of micronanobubbles in the hot fluid. It was observed that compared to the base heat transfer fluid, the nanobubbles heat transfer fluid resulted in a 10–12% increase in heat transfer rate at hot fluid inlet temperatures of 28°C, 30°C, 32°C, 34°C, and 36°C. The method of generation of nanobubbles in HTF and their behavior are also highlighted.